Achieving high energy storage performance of Pb(Lu1/2Nb1/2)O3 antiferroelectric ceramics via equivalent A-site engineering. Issue 13 (October 2022) - Lv, Lingfei; Zhuo, Fangping; He, Chao; Wang, Zujian; Su, Rongbing; Liu, Ying; Yang, Xiaoming; Long, Xifa
Abstract: Manipulating the critical switching field between antiferroelectric (AFE) state and ferroelectric (FE) is an important concept for tuning the energy storage performance of AFEs. As one of the lead-based AFE systems, Pb(Lu1/2 Nb1/2 )O3 promises high potential in the miniaturization of pulsed power capacitors, but the extremely high critical switching field and low induced saturated polarization demonstrate severe drawbacks with respect to temperature stability and flexibility. Here, A-site Ba 2+ doping engineering is used to effectively reduce the critical switching field and improve the saturated polarization in Ba x Pb1- x (Lu1/2 Nb1/2 )O3 (0.01 ≤  x  ≤ 0.08, abbreviated as x Ba-PLN) ceramics. We found the AFE-FE phase transition can be occurred at 80ºC with a high energy storage density of 4.03 J/cm 3 for Ba0.06 Pb0.94 (Lu1/2 Nb1/2 )O3 ceramic. Our results show that Ba 2+ additions destroy the antiparallel structure of AFE phase, and finally reduce the critical switching field, demonstrating a potential alternative to modulate the energy storage performance of AFEs. Graphical Abstract: ga1 Highlights: A-site Ba 2+ doped Pb(Lu1/2Nb1/2)O3 antiferroelectric ceramics were obtained. The Ba 2+ doping engineering is used to effectively reduce the critical switching field and improve the saturated polarization. the AFE-FE phase transition can be occurred at 80C with a high energy storage density of 4.03 J/cm 3 .